2018
DOI: 10.1111/bjd.17152
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation of bacteria to decolonize meticillin-resistant Staphylococcus aureus from human skin

Abstract: The results of this study show that PIB can effectively and safely kill bacteria like MRSA on the skin surface and might have the potential of skin decolonization in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…For example, within this study, good efficacy of at least 6 orders of magnitude was achieved for SAPYR for 0.72 J cm − 2 and 50 µmol l − 1 . However, on ex vivo skin experiments at least 100 µmol l − 1 were applied in combination with at least 30 J cm − 2 in order to achieve sufficient inactivation [15]. Similar findings were reported by another research group where harsher parameters for efficient inactivation had to be applied in an in vivo model [48].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…For example, within this study, good efficacy of at least 6 orders of magnitude was achieved for SAPYR for 0.72 J cm − 2 and 50 µmol l − 1 . However, on ex vivo skin experiments at least 100 µmol l − 1 were applied in combination with at least 30 J cm − 2 in order to achieve sufficient inactivation [15]. Similar findings were reported by another research group where harsher parameters for efficient inactivation had to be applied in an in vivo model [48].…”
Section: Introductionsupporting
confidence: 71%
“…PDI nowadays has a wide range of possible applications. There is plenty of experimental applications in development for example in wastewater treatment [1][2][3][4][5][6][7][8], implementation in antimicrobial coatings [9,10], lowering the microbial load of food and crops [11][12][13][14], decolonization of human skin [15] or in dentistry [16][17][18]. Furthermore, Majiya and colleagues demonstrated sunlight driven water disinfection with a porphyrin immobilized in a chitosan membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Ex vivo skin was inoculated with S. aureus , MRSA, E. coli , or Pseudomonas aeruginosa . The subsequent irradiation yielded a reduction of bacterial cells of up to 5 log 10 steps (36). However, the ex vivo study revealed that the PS concentration and the radiant exposure were clearly higher when compared to experiments in solution.…”
Section: Introductionmentioning
confidence: 99%
“…On human skin samples ex vivo , aPDT with SAPYR [2-((4-pyridinyl)methyl)-1H-phenalen-1-one chloride] (1 mM, 20 mW/cm 2 for 25 min, light dose of 30 J/cm 2 ) reduced the viability of methicillin-resistant Staphylococcus aureus (MRSA) by 3.9 ± 0.3 log 10 orders. aPDT can effectively and safely kill bacteria on the skin surface, and it may have the potential to decolonize the skin in vivo ( 40 ). The photokilling potential of tribenzoporphyrazines had been assessed in vitro at 10 μM concentration and light dose of 30 J/cm 2 , aPDT reduce the growth of Streptococcus pyogenes by over 4.7 log 10 and Staphylococcus epidermidis by over 5.7 log 10 , S. aureus growth by over 5.9 log 10 , as well as MRSA growth by 5.1 log 10 ( 41 ).…”
Section: Anti-infection Effects Of the Photosensitizer-based Therapiesmentioning
confidence: 99%